Analisis Pengaruh Alat Pembayaran Menggunakan Kartu (APMK), Pendapatan Nasional, dan Inflasi Terhadap Konsumsi di Indonesia - Trisan, Yuani; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
There are many reasons why macroeconomic analysis needs to pay attention to household consumption in depth. The first reason, household consumption provides income to the National Income. In most countries, expenditures account for about 60-75 percent of National Income. The second reason is that household consumption has an impact in determining fluctuations in economic activity from one time to another. This study aims:1) To determine and analyze the effect of non- cash transactions, national income, and inflation simultaneously on consumption; and 2) To find out and analyze the effect of non-cash transactions, national income, and inflation partially on consumption. The data used is secondary data in the formof quarterly time series data from 2010-2019 with quantitative data types. analysis technique used is the method of multiple linear regression analysis with the Ordinary Least Square (OLS) model. The results of the study show that: 1) Card- Based Payment Instruments (CBPI), national income, and inflation simultaneously affect consumption in Indonesia; and 2) Card-Based Payment Instruments (CBPI), national income, and inflation partially have a positive and significant effect on consumption in Indonesia.